2022
DOI: 10.1038/s41467-022-33997-0
|View full text |Cite
|
Sign up to set email alerts
|

Phonon downconversion to suppress correlated errors in superconducting qubits

Abstract: Quantum error correction can preserve quantum information in the presence of local errors, but correlated errors are fatal. For superconducting qubits, high-energy particle impacts from background radioactivity produce energetic phonons that travel throughout the substrate and create excitations above the superconducting ground state, known as quasiparticles, which can poison all qubits on the chip. We use normal metal reservoirs on the chip back side to downconvert phonons to low energies where they can no lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We find a monotonic decrease in excess P 1 toward the baseline value following application of the poisoning pulse. In a similar experiment involving injection of pair-breaking phonons into the qubit substrate, Iaia et al observed a QP-induced enhancement of qubit relaxation rate that peaks at a time ∼ 30 µs following application of the poisoning pulse, consistent with diffusive propagation of phonons from the injector junction to the qubit over the ∼4-mm separation between the elements [52]. We take the much faster response of the qubit to the poisoning pulse observed in our experiments as further evidence that coupling of the SFQ driver to the qubit is mediated by photons as opposed to phonons.…”
Section: Dynamics Of Qp Poisoningmentioning
confidence: 94%
See 1 more Smart Citation
“…We find a monotonic decrease in excess P 1 toward the baseline value following application of the poisoning pulse. In a similar experiment involving injection of pair-breaking phonons into the qubit substrate, Iaia et al observed a QP-induced enhancement of qubit relaxation rate that peaks at a time ∼ 30 µs following application of the poisoning pulse, consistent with diffusive propagation of phonons from the injector junction to the qubit over the ∼4-mm separation between the elements [52]. We take the much faster response of the qubit to the poisoning pulse observed in our experiments as further evidence that coupling of the SFQ driver to the qubit is mediated by photons as opposed to phonons.…”
Section: Dynamics Of Qp Poisoningmentioning
confidence: 94%
“…It is known that qubit structures are efficient absorbers of pair-breaking radiation in the mm-wave range [50,51]; for picosecond SFQ pulses with bandwidth of order 100s of gigahertz, the electromagnetic transient could lead to emission of pair-breaking photons that are then absorbed at the qubit junction. We expect to be able to distinguish these two processes by examining the temporal dynamics of QP poisoning in our experiment: while the photonassisted QP poisoning mechanism will lead to immediate suppression of qubit coherence, the phonon mechanism will involve a time delay of order 10s of µs between application of the SFQ pulse and the onset of enhanced QP relaxation associated with the propagation of phonons from the SFQ driver to the qubit [52].…”
Section: Dynamics Of Qp Poisoningmentioning
confidence: 99%
“…Note added.-Recently, we have become aware of a similar experiment by Iaia et al [58]. In their work, the authors compare the impact of high-energy phonons on two separate transmon chips, where one chip has a 10µm-thick Cu film deposited on its backside.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…3.2), as direct means to attenuate the cosmic muon flux. Other initiatives in the field have been addressing the same problem with direct on-chip mitigation strategies, such as lower-gap superconducting quasiparticle traps [11], phonon traps [10], or suspending the device on a membrane [51]. All strategies have evidenced a decrease on the impact of ionizing events on the qubits and/or resonators employed as sensors.…”
Section: Qubit Decoherence Due To Ionizing Radiationmentioning
confidence: 99%
“…Therefore, techniques to mitigate the impact of ionizing radiation events are already necessary today. While on-chip mitigation strategies, such as phonon [10] or quasiparticle traps [11][12][13], are being developed, it is also necessary to understand the physics behind ionizing radiation, particularly the cosmic muon events, in order to find ways to attenuate their flux. In this work, we propose two such methods.…”
Section: Introductionmentioning
confidence: 99%